2001
DOI: 10.1161/01.hyp.37.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Model of an NRE Mediated Tissue-Specific Expression of Murine Renin Genes

Abstract: Abstract-We have used comparative sequence analysis to evaluate a putative silencer element that has been proposed to be involved in the differential tissue-expression of the murine renin genes: Ren-1 and Ren-2. In the mouse, these genes share a similar pattern of tissue-specific renin expression. One significant difference is seen in the submandibular gland (SMG) where renin expression from the Ren-2 locus is 100-fold greater than the expression from the Ren-1 locus. One model proposes that this differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…23 This notion has been chal- lenged by experiments examining renin expression in wildderived mice 24 and by comparative sequence analysis. 25 Recently, Gross and colleagues 4 have reported that the Abd-class of Hox genes also binds to this region and plays a major role in regulating the renin gene. Like other targets of Hox transcription factors, expression of renin exhibits a very specific temporal and spatial profile during fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…23 This notion has been chal- lenged by experiments examining renin expression in wildderived mice 24 and by comparative sequence analysis. 25 Recently, Gross and colleagues 4 have reported that the Abd-class of Hox genes also binds to this region and plays a major role in regulating the renin gene. Like other targets of Hox transcription factors, expression of renin exhibits a very specific temporal and spatial profile during fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, results from analysis of the sequences and expression profiles of natural renin gene variants found in the closely related mouse species Mus hortulanus argue against this. 24 This species also expresses high levels of the Ren-2 gene in the submandibular gland and contains the same sequence elements present in the DBA/2 Ren-2 allele, including the NRE, but does not have the M2 insertion. A recent report by the same group shows that LXR␣, a member of the nuclear receptor superfamily, binds to the CNRE and mediates the cAMP response of the mouse renin promoter.…”
Section: The Lxr␣-binding Sitementioning
confidence: 96%
“…The promoter sequences of mut CNRE Ren-1 C and Ren-2 are not exactly the same (31); the lack of obvious phenotype in the Ren-1 C BAC TgM carrying mut CNRE might be attributed to this difference. In apparent conflict with the proposed model, however, it has been reported that the Ren-2 allele of the Mus hortulanus strain produces abundant Ren-2 mRNA in the SMG, even though its promoter has no insertion next to the NRE (31). Therefore, the mechanism by which locus-specific differences of renin gene expression are achieved in the SMG and kidney remains an open question.…”
Section: Discussionmentioning
confidence: 89%